2014
DOI: 10.1002/2014gc005399
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of cycles in Lava Lake motion and degassing at Erebus Volcano, Antarctica

Abstract: Several studies at Erebus volcano have recorded pulsatory behavior in many of the observable properties of its active lava lake. A strong correlation between the variations in surface speed of the lake and the composition of gas emitted has previously been noted. While previous studies have shown that the SO 2 flux and the surface elevation exhibit pulsatory behavior with a similar period to that of the surface speed and gas composition, suggesting they are linked, a lack of overlap between the different measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 67 publications
1
21
0
Order By: Relevance
“…This not only allows direct observations of surface motion, heat loss, gas chemistry and gas flux (e.g. Spampinato et al 2013;Peters et al 2014), but also direct observations of the lake level, which must respond dynamically to pressure in the magma reservoir feeding the lake, the conduit geometry, the magma ascent rate and the amount of degassing (vesiculation), among other factors (Field et al 2012). Observations of lava lakes thereby provide valuable information that helps in understanding volcano dynamics.…”
mentioning
confidence: 99%
“…This not only allows direct observations of surface motion, heat loss, gas chemistry and gas flux (e.g. Spampinato et al 2013;Peters et al 2014), but also direct observations of the lake level, which must respond dynamically to pressure in the magma reservoir feeding the lake, the conduit geometry, the magma ascent rate and the amount of degassing (vesiculation), among other factors (Field et al 2012). Observations of lava lakes thereby provide valuable information that helps in understanding volcano dynamics.…”
mentioning
confidence: 99%
“…These quasi-periodic variations are remarkably in phase with changes in heat loss at the surface of the lake and changes of the surface velocity of the magma [40]. In a study of thermal imagery of the lake acquired annually from 2004 to 2011, Peters et al [44] and Peters et al [45] showed the cyclic behaviour to be a persistent feature with period varying from 5 to 18 min. Here, we have used the gas composition data to compute time-series changes of equilibrium gas temperatures.…”
Section: Interpreting the Gas Signature At Erebusmentioning
confidence: 96%
“…The chemical composition and flux of the gas plume at Erebus fluctuates cyclically [40,5,33,44,45]. These quasi-periodic variations are remarkably in phase with changes in heat loss at the surface of the lake and changes of the surface velocity of the magma [40].…”
Section: Interpreting the Gas Signature At Erebusmentioning
confidence: 99%
“…Some of these explosions are large enough to partially empty the lake, with ejected material occasionally being thrown clear of the crater (Dibble et al, ; Jones et al, ). During periods of quiescence the lake exhibits a remarkable pulsatory behavior (Oppenheimer et al, ), with its surface motion, surface level, gas composition, and gas flux all varying on a timescale of 10–15 mins (Peters, Oppenheimer, Killingsworth, et al, ). This behavior is thought to reflect the flow dynamics of magma in the conduit feeding the lake (Oppenheimer et al, ; Peters, Oppenheimer, Kyle, et al, ); however, a comprehensive explanation has proved elusive and provides, in part, the motivation for the development of the Eredar radar system.…”
Section: Erebus Volcanomentioning
confidence: 99%
“…A key parameter in studying lava lakes is their surface level. This is indicative of pressure variations in the underlying magmatic system (Patrick et al, 2014) and also fluctuates (typically on shorter time scales) in response to shallower processes such as gas accumulation/release from the lake (Orr & Rea, 2012) and flow dynamics in the conduit (Jones et al, 2015;Peters, Oppenheimer, Killingsworth, et al, 2014).…”
Section: Introductionmentioning
confidence: 99%